Diagnosis and Management of Infections Caused by Enterobacteriaceae Producing Extended-Spectrum b-Lactamase - Audrey Amelia; Agung Nugroho; Paul N Harijanto (Interna Publishing, 2016)
Bacterial resistance to antibiotics is a serious problem worldwide that affect the increment of morbidity and mortality rate; Enterobacteriaceae producing ESBL is one of the causes. However, there are still limited information regarding diagnosis and management of ESBL-E infection. Detection of ESBL-E requires certain steps that are problematic and time consuming. Diagnosis and management of ESBL-E infection have become more and more challenging due to limited diagnostic method available and choice of antibiotics that may be used, along with growing subtyped of ESBL through various of mutations. This article is aimed to give an overview on current situation of ESBL-E infections, with a focus on diagnosis and management of such infection by reviewing several recent studies on related issue.